Penerapan Fahp Pada Pemilihan Metode Pelaksanan Erection Box Girder - Agung Budi Broto; Dul Azis Mei Maulana (Jurnal Poli-Teknologi, 2020)
Many parties are involved in a construction project, so in deciding a method of implementing the box girder erection many criteria are taken into consideration. Consequently, decision making is not easy for decision makers. A simple, frequently-used, and popular method for decision making is Fuzzy-Analytical Hierarchy Process (F-AHP) which is designed to overcome the problem of multi criteria decision making (MCDM) in the subjective assessment process. This study aims to obtain the correct method of implementing the box girder erection to be used. Based on previous research, the criteria for determining box girder erection method are the criteria for job risk, work quality, implementation time, implementation process, work safety, and work costs. The alternatives compared are the tandem crane method and the launching gantry method. The data in this study were collected through questionnaires distributed to the expert parties involved in Jakarta - Cikampek II Elevated Toll Road Project. F-AHP analysis is based on the weighting  of quantitative criteria as a result of normalized calculations and qualitative criteria from the results of the respondents questionnaires which were then made pairwise comparisons assisted by Microsoft Excel software. The results of the analysis show that the occupational safety criteria are the most influential criteria with a weight of 0.454, then followed by job risk criteria (0.169), implementation time (0.119), work quality (0.114), implementation process (0.084), and work costs (0.061). The most appropriate method used in the work of the box girder erection at Jakarta - Cikampek II Elevated Toll Road Project is a launching gantry method with a value of 0.597, while the tandem crane method has a value of 0.403.